2009
DOI: 10.1359/jbmr.090524
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Association Study of 383 Candidate Genes for Volumetric BMD at the Femoral Neck and Lumbar Spine Among Older Men

Abstract: Genetics is a well-established but poorly understood determinant of BMD. Whereas some genetic variants may influence BMD throughout the body, others may be skeletal site specific. We initially screened for associations between 4608 tagging and potentially functional single nucleotide polymorphisms (SNPs) in 383 candidate genes and femoral neck and lumbar spine volumetric BMD (vBMD) measured from QCT scans among 862 community-dwelling white men 65 yr of age in the Osteoporotic Fractures in Men Study (MrOS). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 78 publications
8
41
1
Order By: Relevance
“…rs1513670 polymorphisms of SOST are found to be associated with total hip BMD in healthy Shanghai women [30], but we fail to find this association. We reveal rs851054 polymorphisms of SOST gene significantly correlated to lumbar spine BMD, which are consistent with findings in old American men and postmenopausal Australian women [23,34], but do not conform to results in Korean and Spanish postmenopausal population [36,37].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…rs1513670 polymorphisms of SOST are found to be associated with total hip BMD in healthy Shanghai women [30], but we fail to find this association. We reveal rs851054 polymorphisms of SOST gene significantly correlated to lumbar spine BMD, which are consistent with findings in old American men and postmenopausal Australian women [23,34], but do not conform to results in Korean and Spanish postmenopausal population [36,37].…”
Section: Discussionsupporting
confidence: 69%
“…Compliance to alendronate was evaluated by the number of empty medicine bottles and the remaining tablets at each follow-up. [23,24]. Finally, six tag SNPs and one positive SNP of SOST were selected: rs1234612, rs851054, rs865429, rs851062, rs1513670, rs9902563 and rs1877632 (Supplementary Table 1).…”
Section: Study Participantsmentioning
confidence: 99%
“…In addition, most of these studies have been conducted in women. In contrast, in a relatively large study of men, no significant association was observed between these three genes and volumetric BMD at the femoral neck and lumbar spine (LS) (34) or trabecular and cortical volumetric BMD at the femoral neck. (35) Nevertheless, recently, SNPs located near RANKL, (36) RANK, (37) and OPG (36,38) also have been associated with BMD in genome-wide association studies (GWAS).…”
Section: Introductionmentioning
confidence: 87%
“…Despite this, little information is available regarding the adult skeletal consequences of severe THRA mutations, whilst no individuals with less deleterious THRA mutations or patients with DIO2 mutations have been described. A candidate gene association study of 862 men over 65 years of age investigated the relationships between genetic variation in THRA and BMD at the femoral neck and lumbar spine (25,26), whilst a much larger study investigated the THRA locus in relation to BMD, fracture risk and bone geometry in 27 326 individuals from the Genetic Factors for Osteoporosis (GEFOS) consortium and the Rotterdam Study 1 and 2 populations (21). These studies did not identify any relationships between variation in bone parameters and genetic variation across the THRA locus.…”
Section: Discussionmentioning
confidence: 99%